Tephrosia purpurea: A natural herb/ bliss - Richa Bhardwaj,; Shilpa Shrivastava, (International Journal of Phytomedicine, 2016)
Herbal medicine is in demand due to its fewer side effects and more or better curable techniques. The Tephrosia purpurea, claimed to be healing, curing and lower the various diseases according to Indian medicinal history. This genera species is well known for its therapeutic purpose, in this review we are explaining about the T.P most important characteristics which have been reported. This plant due to its good antioxidant and antibacterial property show best medicine against various diseases such as diuretic, cyto-toxicity and diabetics.